2007
DOI: 10.1007/s00106-006-1480-x
|View full text |Cite
|
Sign up to set email alerts
|

Homöopathie bei akuter Rhinosinusitis

Abstract: The homeopathic product allows an effective and tolerable treatment of acute rhinosinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Nine trials (22%) were rated as B (48,50,53,59,64,67,69,73,75), demonstrating average quality and medium risk of bias. A total of 22 trials (54%) reported both sample size calculations and intention to treat analyses.…”
Section: Methodological Quality Of the Rctsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine trials (22%) were rated as B (48,50,53,59,64,67,69,73,75), demonstrating average quality and medium risk of bias. A total of 22 trials (54%) reported both sample size calculations and intention to treat analyses.…”
Section: Methodological Quality Of the Rctsmentioning
confidence: 99%
“…These trials assessed the symptoms as mild/moderate or severe, or serious or non-serious. A three or four point tolerability scale was used in six trials (49,50,59,84,85,88). Adverse effects were descriptively reported in five trials (49,51,60,78,79).…”
Section: Methodological Quality Of the Rctsmentioning
confidence: 99%
“…Friese and Zabolotnyi [25] reported on a 10-center, double-blind, placebo-controlled trial in adult patients with acute rhinosinusitis that randomized 72 patients to the active agent group and 72 patients to the placebo group. The active drug was the complex homeopathic remedy (Cinnabaris Pentarkan H) that consists of Cinnabaris D3, Echinacea D1, Hydrastis (orangeroot) D3, and potassium dichromate D3.…”
Section: What Can We Deduce From Human Side Effects Documented In Metmentioning
confidence: 99%
“…Уже на протяжении многих лет комплексный натуральный препарат «Циннабсин» с успехом применяется при лечении риносинусита, аденоидита, назофарингита [3,7,8]. Клинические эффекты препарата связывают с восстановлением носового дыхания, разжижением густого носового секрета, активацией механизмов естественного очищения полости носа и околоносовых пазух и, предположительно, с позитивным влиянием на реакции иммунитета, особенно местного характера.…”
unclassified